Long-range extended chains arising from polymerization-driven spontaneous assembly - Min Chen; Dongyang Wang; Ye Zou; Changsheng Chen; Xixian Yang; Lixin Niu; Guan Sheng; Jin Wang; Lucas Q. Flagg; Lee J. Richter; Bethany A. Phillips; Bufan Xiao; et al. (Science, 2026)
A central challenge for conjugated polymers is to achieve long-range order while remaining solution processable, which is essential for matching the electrical performance of their counterparts of crystalline inorganic semiconductors. In this work, we show that n-doped poly(benzodifurandione) (n-PBDF) can undergo polymerization-driven spontaneous assembly (PSA), in which chain growth, chemical doping, and structural ordering are intrinsically coupled, yielding long-range chain extension over hundreds of nanometers. We reveal that the spontaneously formed n-PBDF nanoribbons arise from a self-initiated, convergent growth mechanism driven by cooperative monomer-polymer interactions and stabilized by proton-coupled duplex chains and the polymer’s intrinsic polyelectrolyte character. With long-range extended chains in the nanoribbons, the aligned n-PBDF thin films demonstrate metallic-level conductivity (>10 4 siemens per centimeter).